Pyeloplasty techniques using minimally invasive surgery (MIS) in pediatric patients - Turrà, Francesco (Transl Pediatr, 2016)
Hydronephrosis is the most common presentation of ureteropelvic junction (UPJ) obstruction. We reviewed literature, collecting data from Medline, to evaluate the current status of minimally invasive surgery (MIS) approach to pyeloplasty. Since the first pyeloplasty was described in 1939, several techniques has been applied to correct UPJ obstruction, but Anderson-Hynes dismembered pyeloplasty is established as the gold standard, to date also in MIS technique. According to literature several studies underline the safety and effectiveness of this approach for both trans- and retro-peritoneal routes, with a success rate between 81–100% and an operative time between 90–228 min. These studies have demonstrated the safety and efficacy of this procedure in the management of UPJ obstruction in children. Whether better the transperitoneal, than the retroperitoneal approach is still debated. A long learning curve is needed especially in suturing and knotting.